Assessment of peristomal body profile to ensure the right fit to help prevent leakage - Anne Steen Hansen, & Janice Colwell, & Werner Droste, & Grethe Vendelbo and & Sarah James-Reid (WCET Journal - French Edition, 2022)
Peristomal skin complications (PSCs) are a frequent issue for patients living with an ostomy. A common cause of PSCs is leakage of stomal effluent, which 76% of the patients experience at least once a month. To improve the quality of life (QoL) of people living with an ostomy, the underlying cause and predisposing factors for leakage must be identified and addressed during the selection of an ostomy solution. The aim of this publication is to highlight the importance of assessing the peristomal body profile (PBP) when finding the right ostomy solution and preventing leakage. According to a recent consensus among ostomy care nurses, the pouch seal security and peristomal skin integrity are the most important factors to determine an optimal ostomy solution. Therefore, the patient assessment should include an evaluation of the peristomal area and type of stoma and output. The Peristomal Body Profile Terminology (BPT) was established to assist health practitioners to determine the PBP according to the area around the stoma, as well as the position of the stoma opening in relation to the skin. Incorrect fit with consequential leakage can occur when the PBP is not considered in a structured way when selecting the ostomy solution. The most appropriate ostomy solution will vary according to the patient’s PBP and preference. Therefore, it is crucial for the patients to actively engage in the assessment of their PBP together with the ostomy care nurse, to find the most appropriate ‘fit to body’ solution.